The Influence of the Cooperative Learning Model Think Talk Write Type on the Mathematical Communication Skills of Class VII Students at Imelda Private Middle School Medan - Gabriyeltha Ginting; Wingston Leonard Sihombing (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to determine whether there is an influence of the Think Talk Write (TTW) cooperative learning model on students' mathematical communication skills. This type of research is quantitative research. From the research results, it was obtained that the average value of the class taught using the Think Talk Write cooperative learning model was 86.9 and the class taught using the conventional learning model was 74.7. To test the hypothesis is done using the t test, from the calculation results obtained tcount 5.293 a significance level of 0.000 <0.05, then reject H0 and accept Ha, it is concluded that there is a positive and significant influence between the Think Talk Write cooperative learning model ( TTW) on students' mathematical communication skills. Then an effect size value of 4.08 > 1.00 is obtained which is in the high category.